Pengembangan Media Pembelajaran Digital Berbasis Teknologi Augmented Reality pada Pembelajaran IPAS di Kelas V Sekolah Dasar - Adrianda, Adrianda; Wulandari, Fikhen Tri (Asian Journal of Early Childhood and Elementary Education, 2025)
This study is motivated by the low utilization of technology-based learning media in elementary schools, which results in limited student enthusiasm and engagement. The purpose of this research is to develop an Augmented Reality (AR) technology-based learning medium for the Science and Social Studies (Ilmu Pengetahuan Alam dan Sosial or IPAS) subject, focusing on cultural diversity material for fifth-grade elementary students. The problems were identified through observations and interviews at SDN 41 Seberang Padang Selatan, SDN 32 Pemancungan, and SDN 38 Seberang Padang Selatan, which revealed that both teachers and students rarely used technology-based media in learning activities. This study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected to measure the validity, practicality, and effectiveness of the learning media. The validity test results indicated that the media was highly valid, with scores of 95% from content experts, 100% from language experts, and 97.5% from media experts. The practicality test results showed that the media was highly practical based on feedback from teachers and students across the three schools. The effectiveness test results demonstrated improved student learning outcomes, with post-test scores reaching 100%, 92.5%, and 94.7%, respectively. The conclusion of this study is that the Augmented Reality-based learning media for cultural diversity material in the fifth-grade IPAS subject is appropriate and effective for use in elementary school instruction.